Producción cultural huachafa - Dreifuss Serrano, Cristina (2020)
Contemporary cultural production in our context is characterized by having multiple influences, which result in various final products, eclectic and, in many cases, perceived as inadequate. The terms chicha or huachafo design attitudes, consumer goods, cultural products and even works of art, whose image refer to the mixed characteristics of our society. The combi-nation of traditions, local characters, modernization impulses and the search for belonging to a global environment are some of the forces making the afore-mentioned products possible. When analyzing huachafofrom both a formal and a social point of view, we aim to understand, through everyday events, cultural and artistic manifestation, which are the reasons and mechanisms behind these creations. There is an adap-tation process to new situations, and the construction of our contemporary cities. The huachafo products are, on one side, a key to read who we are. On the other hand, they become part of our everydayness and in this dialogue, there could provoke the construction of a new identity: that of the contemporary Peruvian who “tiene de inga y tiene de mandinga".